The Cost of Counterparty Risk and Collateralization in Longevity Swaps. Issue 2 (6th August 2014) - Biffis, Enrico; Blake, David; Pitotti, Lorenzo; Sun, Ariel
Abstract: Derivative longevity risk solutions, such as bespoke and indexed longevity swaps, allow pension schemes, and annuity providers to swap out longevity risk, but introduce counterparty credit risk, which can be mitigated if not fully eliminated by collateralization. We examine the impact of bilateral default risk and collateral rules on the marking to market of longevity swaps, and show how longevity swap rates must be determined endogenously from the collateral flows associated with the marking‐to‐market procedure. For typical interest rate and mortality parameters, we find that the impact of collateralization is modest in the presence of symmetric default risk, but more pronounced when default risk and/or collateral rules are asymmetric. Our results suggest that the overall cost of collateralization is comparable with, and often much smaller than, that found in the interest rate swaps market, which may then provide the appropriate reference framework for the credit enhancement of both indemnity‐based and indexed longevity risk solutions.